Elucidating the genetic and functional basis of atopic dermatitis and psoriatic arthritis mutilans - Sailan Wang (2025)
Psoriatic arthritis mutilans (PAM) and atopic dermatitis (AD) are two skin disorders. PAM is the most severe and rarest form of psoriatic arthritis, and it is characterized by osteolysis and joint erosion, leading to permanent disability. There are no clear susceptibility genes identified for PAM. AD, a chronic inflammatory skin condition, is influenced by genetic and environmental factors, resulting in skin barrier dysfunction, inflammation, and immune dysregulation. In AD, while genetic risk factors have been explained, these explain only a modest proportion of the heritability. The pathogenesis varies in different populations, such as those of African descent.In this thesis, I explore the genetic and molecular underpinnings of both PAM and AD through next-generation sequencing and functional studies. We aim to uncover novel susceptibility genes involved in disease development. The research goals were achieved by the following four studies included in this thesis.In study I, we performed Next-generation sequencing in the PAM Nordic cohort (n = 61) to study the genetic basis of PAM. We uncovered rare variants in the NADPH oxidase 4 (NOX4) gene and suggested NOX4 as the novel PAM candidate gene. NOX4 is an enzyme responsible for generating reactive oxygen species (ROS) production and is involved in osteoclast differentiation. Functional studies showed that these NOX4 variants upregulate ROS levels in patient- derived osteoclasts, zebrafish models and in HEK293 cells. All the data collected linked NOX4 dysfunction to PAM development. NOX4 is proposed as a candidate susceptibility gene, offering a potential therapeutic target by modulating ROS levels for addressing PAM.In study II, we shifted focus to AD, exploring its genetic origins in an Ethiopian family with multiple affected members. Notably, no mutations in the FLG gene in Ethiopians, highlighting the need to investigate alternative genetic contributors in this population. Whole-genome sequencing revealed two variants co-segregating with the disease in the family, in FLG2 - p.D13Y and NOD2 - p.A918S genes. Further genotyping in the Ethiopian case-control cohort showed significant association with AD for the FLG2 - p.D13Y variant. Additionally, two previously identified NOD2 variants - p.A849V and p.G908R were also linked to AD in Ethiopian AD patients. These findings highlight the importance of FLG2 and NOD2 in the etiology of AD, particularly in African populations.In study III, we further explored the role of the 2-amino ethanethiol dioxygenase (ADO) gene in AD. The idea arises from a previous study in which an AD GWAS variant was linked to the promoter of ADO by published Chromosome conformation capture (Capture Hi-C). The expression of ADO was significantly higher in lesional skin compared to non-lesional skin in AD patients. Zebrafish and in vitro models demonstrated that ADO dysregulation impairs skin barrier function and enhances ROS production and inflammation. This study suggests that ADO plays a critical role in maintaining skin homeostasis, with its dysregulation contributing to AD pathogenesis.In study IV, we investigated the FLG2 gene's role in AD susceptibility in a Swedish population, focusing on the p.S2377X variant. Genotypic analysis in two independent Swedish cohorts revealed a significant association between the FLG2 variant and AD, with reduced FLG2 expression observed in skin tissue from variant carriers. This study underscores the contribution of FLG2 to AD risk, particularly within the Swedish population.Collectively, this thesis broadens the genetic and molecular understanding of PAM and AD. Novel insights were provided by identifying the NOX4 gene as a potential susceptibility factor for PAM, presenting the first significant lead in pinpointing genetic contributors to this severe condition. Furthermore, the thesis highlighted the roles of FLG2, NOD2, and ADO in the etiology of AD, offering the potential genetic cause.Genome sequencing serves as the first tool to identify the genetic cause of the diseases; Subsequent functional studies further provided new insights into disease pathogenesis and potential treatment approaches for managing these diseases.List of scientific papersI. Rare coding variants in NOX4 link high ROS levels to psoriatic arthritis mutilansSailan Wang, Pernilla Nikamo, Leena Laasonen, Bjorn Gudbjornsson, Leif Ejstrup, Lars Iversen, Ulla Lindqvist, Jessica J Alm, Jesper Eisfeldt, Xiaowei Zheng, Sergiu-Bogdan Catrina, Fulya Taylan, Raquel Vaz, Mona Ståhle and Isabel Tapia-Paez EMBO Molecular Medicine.2024;16(3):596-615. https://doi.org/10.1038/s44321-024-00035-zII. Uncommon variants in FLG2 and NOD2 are associated with atopic dermatitis in the Ethiopian populationSailan Wang, Julia K. Elmgren, Jesper Eisfeldt, Samina Asad, Marlene Ek, Kassahun Bilcha, Annisa Befekadu, Carl-Fredrik Wahlgren, Magnus Nordenskjöld, Fulya Taylan, Isabel Tapia-Paez* and Maria Bradley *. JID Innovations. 2024 Apr 29;4(4):100284. https://doi.org/10.1016/j.xjidi.2024.100284III. The role of the cysteamine dioxygenase (ADO) gene in atopic dermatitisSailan Wang, Raquel Vaz, Josefin Lysell, Jesper Eisfeldt, Pelin Sahlén, Samina Asad, Carl-Fredrik Wahlgren, Magnus Nordenskjold, Maria Bradley* and Isabel Tapia-Paez *. [Manuscript]IV. The FLG2 gene is associated with atopic dermatitis in Swedish patientsSailan Wang, Mahsa Tayefi, Axel Svedbom, Samina Asad, Carl- Fredrik Wahlgren, Magnus Nordenskjold, Emma Johansson, Isabel Tapia-Paez* and Maria Bradley* [Manuscript]* Authors contributed equally